Clinical and economic burden of wound care in the tropics: a 5‐year institutional population health review. Issue 3 (9th March 2020) - Lo, Zhiwen J.; Lim, Xuxin; Eng, Diane; Car, Josip; Hong, Qiantai; Yong, Enming; Zhang, Li; Chandrasekar, Sadhana; Tan, Glenn W. L.; Chan, Yam M.; Sim, Seow C.; Oei, Chien W.; et al.
Abstract: The aim of this study is to evaluate the clinical and economic burden of wound care in the Tropics via a 5‐year institutional population health review. Within our data analysis, wounds are broadly classified into neuro‐ischaemic ulcers (NIUs), venous leg ulcers (VLUs), pressure injuries (PIs), and surgical site infections (SSIs). Between 2013 and 2017, there were a total of 56 583 wound‐related inpatient admissions for 41 461 patients, with a 95.1% increase in wound episodes per 1000 inpatient admissions over this period (142 and 277 wound episodes per 1000 inpatient admissions in 2013 and 2017, respectively). In 2017, the average length of stay for each wound episode was 17.7 days, which was 2.4 times that of an average acute admission at our institution. The average gross charge per wound episode was USD $12 967. Among the 12 218 patients with 16 674 wound episodes in 2017, 71.5% were more than 65 years of age with an average Charlson Comorbidity Index (CCI) of 7.2. Half (51.9%) were moderately or severely frail, while 41.3% had two or more wound‐related admission episodes. In 2017, within our healthcare cluster, the gross healthcare costs for all inpatient wound episodes stand at USD $216 million within hospital care and USD $596 000 within primary care. Most NIU patients (97.2%) had diabetes and they had the most comorbidities (average CCI 8.4) and were the frailest group of patients (44.9% severely frail). The majority of the VLU disease burden was at the specialist outpatient setting, with the average 1‐year VLU recurrence rate at 52.5% and median time between healing and recurrence at 9.5 months. PI patients were the oldest (86.5% more than 65 years‐old), constituted the largest cohort of patients with 3874 patients at an incidence of 64.6 per 1000 admissions in 2017, and have a 1‐year all‐cause mortality rate of 14.3%. For SSI patients, there was a 125% increase of 14.2 SSI wound episodes per 1000 inpatient admissions in 2013 to 32.0 in 2017, and a 413% increase in wound‐related 30‐day re‐admissions, from 40 in 2013 (4.1% of all surgeries) to 205 (8.3% of all surgeries) in 2017. The estimated gross healthcare cost per patient ranges from USD $15789–17 761 across the wound categories. Similar to global data, there is a significant and rising trend in the clinical and economic burden of wound care in Tropics.